Hybridisation among groupers (genus Cephalopholis) at the eastern Indian Ocean suture zone: taxonomic and evolutionary implications - Payet, S.; Hobbs, Jean-Paul; Di Battista, Joseph; Newman, Stephen; Sinclair-Taylor, T.; Berumen, M.; McIlwain, Jennifer (Springer Verlag, 2016)
Hybridisation is a significant evolutionary process that until recently was considered rare in the marine environment. A suture zone in the eastern Indian Ocean is home to numerous hybridising sister species, providing an ideal opportunity to determine how hybridisation affects speciation and biodiversity in coral reef fishes. At this location, hybridisation between two grouper (Epinephelidae) species: Cephalopholis urodeta (Pacific Ocean) and C. nigripinnis (Indian Ocean) was investigated to determine the genetic basis of hybridisation and to compare the ecology and life history of hybrids and their parent species. This approach aimed to provide insights into the taxonomic and evolutionary consequences of hybridisation. Despite clear phenotypic differences, multiple molecular markers revealed hybrids, and their parent species were genetically homogenous within and (thousands of kilometres) outside of the hybrid zone. Hybrids were at least as fit as their parent species (in terms of growth, reproduction, and abundance) and were observed in a broad range of intermediate phenotypes. The two species appear to be interbreeding at Christmas Island due to inherent biological and ecological compatibilities, and the lack of genetic structure may be explained by three potential scenarios: (1) hybridisation and introgression; (2) discordance between morphology and genetics; and (3) incomplete lineage sorting. Further molecular analyses are necessary to discriminate these scenarios. Regardless of which applies, C. urodeta and C. nigripinnis are unlikely to evolve in reproductive isolation as they cohabit where they are common (Christmas Island) and will source congeneric mates where they are rare (Cocos Keeling Islands). Our results add to the growing body of evidence that hybridisation among coral reef fishes is a dynamic evolutionary factor. © 2016 Springer-Verlag Berlin Heidelberg.